2016
DOI: 10.1126/science.aad3747
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of lipoprotein signal peptidase II action and inhibition by the antibiotic globomycin

Abstract: With functions that range from cell envelope structure to signal transduction and transport, lipoproteins constitute 2 to 3% of bacterial genomes and play critical roles in bacterial physiology, pathogenicity, and antibiotic resistance. Lipoproteins are synthesized with a signal peptide securing them to the cytoplasmic membrane with the lipoprotein domain in the periplasm or outside the cell. Posttranslational processing requires a signal peptidase II (LspA) that removes the signal peptide. Here, we report the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
127
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(133 citation statements)
references
References 32 publications
6
127
0
Order By: Relevance
“…Residues in TM4 show NOEs to the DMPC fatty acid methylene chain at 1.25 ppm only when in protonated DMPC samples (Figure 7D). Comparison of our secondary structure of LspA in complex with globomycin with the recently published crystal structure (Vogeley et al, 2016) confirms the presence of these β-strands which lie on the periplasmic side of the membrane and the shorter TM4. In addition, the backbone assignment allows us to confirm that many of the residues that become visible upon forming a complex with globomycin (Figure 1E and 1F) are located in and around the globomycin binding site of LspA such as A51 and N53 in the ‘pH region’.…”
Section: Resultssupporting
confidence: 84%
“…Residues in TM4 show NOEs to the DMPC fatty acid methylene chain at 1.25 ppm only when in protonated DMPC samples (Figure 7D). Comparison of our secondary structure of LspA in complex with globomycin with the recently published crystal structure (Vogeley et al, 2016) confirms the presence of these β-strands which lie on the periplasmic side of the membrane and the shorter TM4. In addition, the backbone assignment allows us to confirm that many of the residues that become visible upon forming a complex with globomycin (Figure 1E and 1F) are located in and around the globomycin binding site of LspA such as A51 and N53 in the ‘pH region’.…”
Section: Resultssupporting
confidence: 84%
“…We do not yet understand the basis for this permeability. The cpxA24 Δlpp ΔrcsB strain and its ΔlolA/B/ AB derivatives cells also remained sensitive to the Lsp signal peptidase inhibitor globomycin (45) (Table S1). Lsp activity requires that substrate prelipoproteins are first diacylated (14).…”
Section: The Cpx Response Monitors Lipoprotein Trafficking and Protectsmentioning
confidence: 99%
“…95 Structure activity relationship studies demonstrated that the hydroxyl of the Ser residue was critical for antibacterial activity. 96 The crystal structure of globomycin in complex with LspA, a SP-II from P. aeruginosa, 97 demonstrates that this Ser is in contact with the proposed catalytic Asp124 and Asp143 of the active site, and that the antibiotic occupies the substrate signal peptide-binding site. This structure should help to guide additional improvements to globomycin, to increase efficacy.…”
Section: Bacterial Proteases Untapped Antimicrobial Drug Targetsmentioning
confidence: 99%